Disease-phase-specific resource utilization and healthcare costs in metastatic colorectal cancer: a subgroup analysis of the finnish RAXO study - Kontiainen, Joel; Lehtomäki, Kaisa; Muhonen, Timo; Heervä, Eetu; Ålgars, Annika; Ristamäki, Raija; Stedt, Hanna; Lamminmäki, Annamarja; Kallio, Raija; Salminen, Tapio; Kuopio, Teijo; Osterlund, Emerik; et al. (Taylor and Francis Group, 2026)
Introduction
Metastatic colorectal cancer (mCRC) represents a growing burden on healthcare, yet comprehensive data on treatment costs across different disease phases remain limited. This study aims to estimate hospital resource utilization and costs of treating mCRC patients according to international up-to-date guidelines.
Materials and methods
The RAXO study aimed at maximising metastasectomy with repeated centralized assessment of resectability (inclusion 2012–2018). Cost data from the six largest Finnish hospital districts (n = 941) in RAXO were collected from mCRC diagnosis to death or the end of 2021. All patient costs were characterized day-by-day to diagnostic, curative, remission, palliative SACT, treatment break, or end-of-life disease phases. The resource utilization and mean costs, in 2021 euros, were calculated per patient per month (PPPM).
Results
The mean PPPM cost for treating mCRC patients was 2323€, when 37% had curative-intent metastasectomy. On average, each month included 0.7 ward days, 1.9 outpatient and 0.1 emergency visits. Outpatient care accounted for 64% of costs, inpatient care for 34%, and emergency room visits for 2%. The higher costs during disease phases involving active tumour-directed treatments (2963€–3059€/PPPM) were balanced by lower costs during remission and treatment break (453€–560€/PPPM). Pharmacy, ward, operating room, and outpatient costs (39%/18%/15%/15%, respectively) were the main drivers for internal hospital billing.
Conclusions
Resource utilization, costs, and cost drivers varied 8-fold between disease phases. Outpatient care accounted for two-thirds, and inpatient care accounted for one-third of costs.